2011
DOI: 10.1017/s1041610211001037
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological correlates of apathy in mild cognitive impairment and Alzheimer's disease: the role of executive functioning

Abstract: Apathy is related to executive dysfunction in the early phases of cognitive decline. In particular, in the prodromal phase of AD, apathy seems to be characterized by poor initiating. In the more advanced stages of cognitive deterioration, associations between apathy and specific neuropsychological correlates may be obscured by the more severe neuropathology. Awareness of apathy in the early phase of cognitive impairment may help in early diagnosis of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 33 publications
(52 reference statements)
2
39
0
6
Order By: Relevance
“…These results suggested that, independently from clinical diagnosis, apathetic patients showed relevant executive impairments, in line with most previous studies [14,15,20,21,23,25,26]. In other terms, the present data indicated a strong association between apathy and alterations of cognitive functions mediated by prefrontal cortex, since apathetic and non-apathetic patients were matched for age, educational level and severity of general cognitive decline.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results suggested that, independently from clinical diagnosis, apathetic patients showed relevant executive impairments, in line with most previous studies [14,15,20,21,23,25,26]. In other terms, the present data indicated a strong association between apathy and alterations of cognitive functions mediated by prefrontal cortex, since apathetic and non-apathetic patients were matched for age, educational level and severity of general cognitive decline.…”
Section: Discussionsupporting
confidence: 92%
“…Apathy has also been observed in Alzheimer's disease (AD) since its early stages [24], and is associated with low functional autonomy, severe executive dysfunction and fast cognitive and functional decline [24][25][26][27]. Brain imaging studies in AD reported a significant association between apathy and abnormal perfusion in the frontal cortex and in the cingulate area [28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Investigators have also suggested that apathy may contribute to cognitive impairment more significantly than does depression in AD [3,7,16]. Specifically, Kuzis et al [16] found that apathy was associated with significantly worse performance on measures of verbal memory, confrontation naming, nonverbal reasoning, and verbal fluency.…”
Section: The Impact Of Depression and Apathy On Cognition In Admentioning
confidence: 99%
“…Indeed, different executive processes contribute to successfully manage adaptation to the environment: abilities to make decisions, initiate tasks, generate adaptation strategies and judge their accuracy, self-correct and complete tasks effectively. Impairment of these executive processes was shown to be related to apathy which is an early symptom in AD [13].…”
Section: Introductionmentioning
confidence: 99%